Size and persistence matters: Wage and employment insurance at the micro level - Martin Kerndler (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
Firms provide substantial insurance against wage fluctuations and job loss. This paper studies how the interaction between shock size and persistence affects the firm's ability to insure workers against idiosyncratic firm-level shocks. Using linked employer-employee data from Germany, I find that wages respond largely symmetrically to positive and negative permanent shocks. Whereas transitory shocks lead to upward wage rigidity. Individual layoff probabilities only increase in response to negative permanent shocks. Interestingly, wage cuts and job loss after negative shocks are limited to blue-collar workers. Whereas white-collar workers are fully insured against negative shocks both in terms of wages and employment.
Keywords: C33; D22; J33; J41; 330; wage insurance; layoffs; linked employer-employee data; Kalman filter